CONVENTIONAL TAXONOMY AND TREATMENT ETIQUETTE OF KAMALA W.S.R.TO MODE OF ACTION OF NAVAYAS LAUHA CHURNA ON SHAKHASHRIT KAMALA (HEPATO-CELLULAR JAUNDICE) - Kamleshwar, Prasad; Brijesh, Kumar; Pravin Kumar, Rai; Aruna Kumar, Panigrahy (International Journal of Ayurveda and Pharma Research, 2015)
The scientific taxonomy of disease make easy to study, recognition of etiology, diagnosis and planning of treatment of any ailment. The traditional cataloging of diseases have been described in traditional system of medicine is very scientific as well as practical also. Like classification of other ailment, Kamala has been classified basically in various groups like Koshthashrita (haemolytic jaundice) & Shakhashrita (hepato-cellular jaundice), Swatantra (independent) and Partantra (manifest as a complication of another disease), Bahupitta (due to excess generation of bilirubin) and Alpapitta (due to retention of bilirubin). But in this article, the elaborated taxonomy of Kamala is described on the behalf of four types of Samprapti i.e. Vidhi, Vikalpa, Pradhanya and Bala which have great importance in diagnosis and management of Kamala ailment. Everyone knows that abolition of etiology and cleavage of pathological chain of ailment is the steady and complete healing of disease. The treatment protocol of Kamala is entirely based on this theory. There are two segment of treatment of Kamala, first is nonspecific which is common and applicable for all kinds of Kamala and second is specific treatment which is explicit for definite types of Kamala. In Ayurvedic pharmacology, the mode action of drugs and how to cleavage the pathogenesis of ailment is not described but here it is illustrated very clearly and in a mannered way. The Navayas lauha churna has three groups of herbal drugs i.e. Trimada, Trikatu and Triphala and one group of Lauha bhasma. Each groups of drugs of this medicine; where (at which step of pathogenesis) and how to act and cleavage the pathogenesis of Shakhashrita kamal (hepato-cellular jaundice) are narrated with scientific, logical and evidence based discussion and as well as institution of liaison with contemporary science.